2011
DOI: 10.1007/s11095-011-0558-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Nanoparticles for Increased Oral Bioavailability and Rapid Absorption Using Celecoxib as a Model of a Low-Solubility, High-Permeability Drug

Abstract: PurposeTo demonstrate drug/polymer nanoparticles can increase the rate and extent of oral absorption of a low-solubility, high-permeability drug.MethodsAmorphous drug/polymer nanoparticles containing celecoxib were prepared using ethyl cellulose and either sodium caseinate or bile salt. Nanoparticles were characterized using dynamic light scattering, transmission and scanning electron microscopy, and differential scanning calorimetry. Drug release and resuspension studies were performed using high-performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 24 publications
1
69
0
Order By: Relevance
“…This increase in systemic exposure, which was accompanied by lower T max values of Cx/bCN, indicates that this formulation was characterized by more rapid and efficient Cx dissolution in the GI tract. This outcome may stem from the fact that the Celebra ® formulation contained micron-sized crystalline drug (11,38) while Cx in Cx/bCN is nano-sized and amorphous (15). Enhanced dissolution rate and oral bioavailability of Cx in an amorphous nano-formulation was previously reported (12).…”
Section: Bioavailability Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…This increase in systemic exposure, which was accompanied by lower T max values of Cx/bCN, indicates that this formulation was characterized by more rapid and efficient Cx dissolution in the GI tract. This outcome may stem from the fact that the Celebra ® formulation contained micron-sized crystalline drug (11,38) while Cx in Cx/bCN is nano-sized and amorphous (15). Enhanced dissolution rate and oral bioavailability of Cx in an amorphous nano-formulation was previously reported (12).…”
Section: Bioavailability Analysismentioning
confidence: 95%
“…At concentrations above its critical micellization concentration (CMC, 0.5-2 mg/mL at pH∼7, 25°C), bCN self-assembles in water into nanometric micelles (∼20-25 nm in diameter) having a hydrophobic core and a hydrophilic corona (17). The bCN structural and physicochemical properties facilitate its application in drug delivery (18)(19)(20), and bCN has been used for encapsulation of hydrophobic chemotherapeutics (21)(22)(23), However, our formulation is quite different from these, and also from the Cx and casein-based formulation described recently (11). We assumed that in our formulation, bCN can allow high drug loading and encapsulation efficiency since the drug is encapsulated within bCN micelles present in significantly higher concentrations than its CMC.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This complies with the typical nature of solid particles formed using emulsion or precipitation methods, due to the favorable energetics associated with minimization of surface area. 30 It was also reported that spherical nature of the formed NPs itself provided favorable controlled release of incorporated drug where it provided a long diffusion pathway. 17 Differential scanning calorimetry DSC thermograms of PX, P188, EC, their PM, and P188/0.2 are presented in Figure 3.…”
Section: Scanning Electron Microscopymentioning
confidence: 96%
“…Nanonization of pharmacons offers a great possibility to increase their solubility (Ambrus et al, 2009) and to enhance permeability through mucosal barriers (Morgen et al, 2012). Nano-sized drug particles with carriers can overcome the resistance offered by biological barriers .…”
Section: Drug Nanoparticles -Innovations In Pharmaceutics With Nanotementioning
confidence: 99%